Investment Feasibility Analysis of Asset Addition at PT PLN (Persero) ULP Pangkep Based on Financial Indicators - Ummul Chair; Baharuddin Semmalia; Aryati Arfah; Muhammad Arif; Andi Muhammad Anshar (Universitas Trunodjoyo Madura, 2026)
Investment decisions in electricity infrastructure require comprehensive financial evaluation because they involve significant capital and long-term commitments, especially amidst the continuously growing demand for reliable electrical energy. This study aims to analyze the feasibility of asset addition investment planning at PT Perusahaan Listrik Negara (Persero) ULP Pangkep using financial feasibility indicators to ensure the optimal allocation of resources. The research applies a descriptive case study method using secondary data obtained from the company's internal investment planning documents, estimated cash flows, and historical financial information. The financial investment feasibility was rigorously analyzed using four main capital budgeting techniques: Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI). The analysis results indicate that the proposed asset addition investment is highly financially feasible and practically viable. Specifically, the investment generates a substantial positive economic benefit, provides an acceptable return period that mitigates long-term risks, and produces investment indicator values that comfortably exceed the minimum required feasibility criteria. Ultimately, the findings provide robust, data-driven recommendations for the management in making strategic investment decisions to continuously improve electricity service reliability, enhance distribution network performance, and expand overall operational capacity.